2006
DOI: 10.1103/physreve.74.011919
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the tunneling conductance across DNA bases

Abstract: Characterization of the electrical properties of the DNA bases (adenine, cytosine, guanine, and thymine), in addition to building the basic knowledge on these fundamental constituents of a DNA, is a crucial step in developing a DNA sequencing technology. We present a first-principles study of the current-voltage characteristics of nucleotidelike molecules of the DNA bases, placed in a 1.5 nm gap formed between gold nanoelectrodes. The quantum transport calculations in the tunneling regime are shown to vary str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 26 publications
3
65
0
Order By: Relevance
“…The physical-chemical modalities of the above-mentioned sensors are hot topic for the present, they are systematically studied by several groups using theoretical approaches and cause vivid debates in the literature (see, for example, works [124][125][126][127][128][129][130][131] and the references therein).…”
Section: Medical Applications Of Single Molecule Conductancementioning
confidence: 99%
“…The physical-chemical modalities of the above-mentioned sensors are hot topic for the present, they are systematically studied by several groups using theoretical approaches and cause vivid debates in the literature (see, for example, works [124][125][126][127][128][129][130][131] and the references therein).…”
Section: Medical Applications Of Single Molecule Conductancementioning
confidence: 99%
“…13 On the theoretical front, the transverse tunneling conductance across nucleobases placed between two gold electrodes has been actively investigated and debated. 4,7,[16][17][18][19][20][21] Interestingly, recently some special attention has been dedicated to exploring graphene nanopore, graphene nanoribbon and carbon nanotubes (CNT) as potential electrodes materials. [22][23][24] Despite these many works, a key question still remains largely unanswered, namely, how can one enhance the nucleotide-electrode interaction to a point where the transmigration is still possible, but the geometrical fluctuations are sufficiently suppressed to allow unambiguous single nucleotide recognition.…”
Section: Introductionmentioning
confidence: 99%
“…a large noise and poor signal-to-noise ratio in the transversal nonresonant tunneling conductance. For example, it is found that the variation in the conductance due to the geometry of the base relative the electrode can easily override the difference between different types of nucleotide [6,8]. Therefore, a full control of the DNA translocation and localization as it threads the nanopore becomes a primary concern for the DNA sequencing techniques using synthetic nanopores [23][24][25].…”
mentioning
confidence: 99%
“…A ssDNA polymer is negatively charged along its phosphorous backbone, with one elementary charge per monomer. The basic idea of these methods is electrical detection of the DNA sequences, either by reading the electron tunneling current measured across the pore transversally to the translocating DNA varies with a base passing through the pore between the electrodes [2][3][4][5][6][7][8] or by reading the ionic current through a pore while a single DNA polymer is translocated through a nanopore of molecular diameter or a nanogap by electrophoretic field, one base at a time [9][10]. The measurement and computation of the conductance of a single molecule is an attractive concept for molecular detection because single-molecule conductance may be governed at this lengthscale by the molecule intrinsic electronic properties [1,11].…”
mentioning
confidence: 99%